(untitled) (Research, Society and Development, 2019)
The present work has the objective of drawing some considerations about the state performance before those who, under its custody, started a hunger strike and also discuss the right that these individuals have in using their own bodies as an instrument of manifestation and protest and the caused by this type of manifestation. Therefore, a study was made not only on the foundations that legitimize state performance on these individuals, but also on the foundations that impose limitations to this exercise of power. The considerations presented here, based on literature review, allow us to analyze the performance of the state power against the fundamental rights of the detainee, who initiates a hunger strike. It was possible to observe that the abstention of the State in interventions in the exercise of the right of free manifestation fulfills the function of prohibiting interference in the individual juridical sphere, in order to avoid aggressions within the scope of individual freedoms. It was also found that it is for the State to recognize the subject the legal capacity to act in his favor, placing him, in the position of guarantor of that benefit. The limit of this is the fundamental rights founded on the notion of the dignity of the human person. As for the aspects related to health will have several causing and / or aggravating existing pathologies and taking the age as an influencing factor of this response.